How dynamic capabilities facilitate the survivability of social enterprises: A qualitative analysis of sensing and seizing capacities. (1st November 2020) - Ince, Inan; Hahn, Rüdiger
ABSTRACT: The purpose of this study is to identify how dynamic capabilities facilitate the survivability of social enterprises amid the tensions that these companies typically face. We employ an abductive analysis of 18 social enterprises in Germany and propose three capabilities: (1) establishing passive communication with the stakeholders enables inexpensive and direct sensing and shaping of opportunities; (2) selective signaling helps access critical resources and capitalize on the business model to seize opportunities, whereas (3) integrating collaborators expands the company's reach and strengthens strategic decision-making. Finally, key implications are drawn for dynamic capabilities in social enterprises.